Universities and the dilemmas of educational quality in the context of globalization - Guzmán Esquivel, Danny (2019)
The progressive weakening of state in Latin America has led us to times ofcrisis, where the constant pressure from the powers at a global level haveforced governments to consider situations such as the opening of marketsand with this the breakdown of those institutions in charge to watch over thesocial goodness. Immersed in an advanced capitalist system that constantlyobscures and transforms reality, we see how the educational field does notescape from such circumstances affecting not only its structure, but also itsdirection. Because of this, we could think of an education that instead of promotingthe integration of the subject to a system, looks for the emancipationof the human being, but not in terms of industry and capital, but aim at theemancipation of the human being towards the development of their tastesand abilities, leading us to new alternatives.